Law on cultural heritage - The National Assembly (2001)
This Law provides for cultural heritage. Cultural heritage provided for in this Law includes intangible and tangible cultural heritages, which are spiritual and material products having historical, cultural or scientific value and handed down from generation to generation in the Socialist Republic of Vietnam.